Simultaneous C and N Removal from Saline Salmon Effluents in Filter Reactors Comprising Anoxic-Anaerobic-Aerobic Processes: Effect of Recycle Ratio - Huilinir-Curio, C (2014)
Salmon processing generates saline effluents with high protein load. To treat these effluents, three compact tubular filter reactors were installed and an integrated anoxic/anaerobic/aerobic process was developed with recycling flow from the reactor s exit to the inlet stream in order to save organic matter (OM) for denitrification. The reactors were aerated in the upper section with recycle ratios (RR) of 0, 2, and 10, respectively, at 30°C. A tubular reactor behave as a plug flow reactor when RR = 0, and as a mixed flow reactor when recycle increases, thus, different RR values were used to evaluate how it affects the product distribution and the global performance. Diluted salmon process effluent was prepared as substrate. Using loads of 1.0 kg COD m -3d-1 and 0.15 kg total Kjeldahl nitrogen (TKN) m -3d-1 at HRT of 2 d, 100% removal efficiencies for nitrite and nitrate were achieved in the anoxic-denitrifying section without effect of the dissolved oxygen in the recycled flow on denitrification. Removals >98% for total organic carbon (TOC) was achieved in the three reactors. The RR had no effect on the TOC removal; nevertheless a higher efficiency in total nitrogen removal in the reactor with the highest recycle ratio was observed: 94.3% for RR = 10 and 46.6% for RR = 2. Results showed that the proposed layout with an alternative distribution in a compact reactor can efficiently treat high organic carbon and nitrogen concentrations from a saline fish effluent with OM savings in denitrification. © 2014 Copyright Taylor and Francis Group, LLC.